Analgesic activity of ethanolic extract of Manihot esculenta Crantz leaves in mice - Miladiyah, Isnatin (Universa Medicina, 2011)
Cassava (Manihot esculenta Crantz) leaves have long been used as a vegetable in many countries and empirically as a febrifuge. The aim of the present study was to evaluate the analgesic activity of an ethanolic extract of cassava leaves in mice. Thirty Balb/c mice (20-30 g, 2-3 months old) were randomly divided into 6 groups. Group I was given distilled water 1 mL as negative control, group II paracetamol 65 mg/kgBW as positive control, and group III-VI received an ethanolic extract of cassava leaves in 4 doses, i.e. 12.8 mg/kgBW, 25.6 mg/kgBW, 51.3 mg/kgBW, and 102.6 mg/kgBW, respectively. All interventions were administered as a single dose by oral route on a given day. Acetic acid 0.6% (w/v) was used as a pain inductor. Analgesic activity was measured by counting the percentage of writhing movements as a measure of the analgesic effectÂ  produced by each intervention. Data were analyzed with one-way Anova to compare analgesic activity between treatment groups. The results showed that groups treated with ethanolic extract of cassava leaves at dosages of 12.8 mg/kgBW, 25.6 mg/kgBW, 51.3 mg/kgBW, and 102.6 mg/kgBW had an analgesic activity of 59.2%; 73.9%; 62.1%; and 55.9%, respectively. On statistical analysis there were significant differences (p=0.00) between these treatments compared to the negative control, but no significant differences (p>0.05) with the positive control (paracetamol). It may be concluded that the analgesic effect of an ethanolic extract of cassava (Manihot esculenta Crantz) leaves in mice was of similar potency as paracetamol.